Dampak Good Corporate Governance (GCG) Terhadap Kecurangan: Sudut Pandang dari Studi Literatur - Rahma Umnun Mabyuni; Ilham Ramadhan Ersyafdi; Fitriah Ulfah (Ikatan Cendekiawan Muda Akuntansi (ICMA), 2025)
Corruption, financial reporting fraud and asset misappropriation are serious problems that threaten the integrity and sustainability of companies in various sectors, including the public and banking sectors. Good Corporate Governance (GCG) is a strategic solution in preventing and reducing these practices through the application of principles such as transparency, accountability, responsibility, independence, and fairness. GCG not only functions as a system that regulates relations between stakeholders but also as an effective control mechanism to improve company performance while preventing fraudulent acts. This study uses a literature study method to examine the role of GCG in preventing three dimensions of fraud, namely corruption, financial reporting fraud and asset misappropriation. The results of the study indicate that the implementation of good GCG can minimize the risk of fraud, increase management transparency, and create an organizational culture that is conducive to sustainable company management.